2018
DOI: 10.1016/j.humimm.2018.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of persistent and cleared preformed HLA DSA on kidney transplant outcomes

Abstract: Preformed HLA donor-specific antibodies (DSA) only detected with Luminex have been associated with increased risk of antibody-mediated rejection (ABMR) and graft failure after kidney transplantation (KT). Their evolution after KT may modify this risk. We analyzed postransplant evolution of preformed DSA identified retrospectively and their impact on outcomes of 370 KT performed 2006-2014. Antibodies were monitored prospectively at 1-3-5 years after KT and if any dysfunction. Early acute ABMR was more frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 32 publications
6
29
0
Order By: Relevance
“…This confirms the suggestion from previous but much smaller studies that reported on resolution of preDSA after transplantation in 31%-67% of patients. 7,8,22 In addition, we confirmed that higher MFI values of the immunodominant preDSA were an independent determinant of preDSA persistence after transplantation. 7,8 Finally, and for the first time, we illustrated that predominantly DQ preDSA persisted after transplantation, which was not uncovered in prior studies potentially due to the lack of high-resolution or complete HLA typing data of the transplant pairs and preDSA misclassification.…”
Section: Discussionsupporting
confidence: 74%
“…This confirms the suggestion from previous but much smaller studies that reported on resolution of preDSA after transplantation in 31%-67% of patients. 7,8,22 In addition, we confirmed that higher MFI values of the immunodominant preDSA were an independent determinant of preDSA persistence after transplantation. 7,8 Finally, and for the first time, we illustrated that predominantly DQ preDSA persisted after transplantation, which was not uncovered in prior studies potentially due to the lack of high-resolution or complete HLA typing data of the transplant pairs and preDSA misclassification.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, Marfo et al demonstrated that recipients with persistent pDSAs experienced more acute and chronic rejection (p = 0.006) than recipients with reversed pDSA [18]. The independent risk factor associated with persistence of pDSA was pre-transplant MFI, as shown by Redondo-Pachon et al, and class II DSAs persisted more frequently [19]. Similarly, we found that persistent pDSAs possessed higher MFIs.…”
Section: Persistent Pdsassupporting
confidence: 82%
“…The negative impact of preformed donor‐specific antibodies (DSAs) in isolated KT is well known, ( 1‐5 ) and the risk of hyperacute kidney rejection is high in the presence of a positive complement‐dependent cytotoxicity crossmatch (CDCXM). ( 6 ) Also, the presence of pretransplant DSAs has been associated with patient mortality.…”
mentioning
confidence: 99%